Biogenic Synthesis of Multifunctional Silver Oxide Nanoparticles (Ag2ONPs) Using Parieteria alsinaefolia Delile Aqueous Extract and Assessment of Their Diverse Biological Applications - Zakir Ullah; Farhat Gul; Javed Iqbal; Banzeer Ahsan Abbasi; Sobia Kanwal; Wadie Chalgham; Mohamed A. El-Sheikh; Sibel Emir Diltemiz; Tariq Mahmood (Microorganisms, 2023)
Green nanotechnology has made the synthesis of nanoparticles a possible approach. Nanotechnology has a significant impact on several scientific domains and has diverse applications in different commercial areas. The current study aimed to develop a novel and green approach for the biosynthesis of silver oxide nanoparticles (Ag2ONPs) utilizing Parieteria alsinaefolia leaves extract as a reducing, stabilizing and capping agent. The change in color of the reaction mixture from light brown to reddish black determines the synthesis of Ag2ONPs. Further, different techniques were used to confirm the synthesis of Ag2ONPs, including UV-Visible spectroscopy, Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscope (SEM), Energy-dispersive X-ray spectroscopy (EDX), zeta potential and dynamic light scattering (DLS) analyses. The Scherrer equation determined a mean crystallite size of ~22.23 nm for Ag2ONPs. Additionally, different in vitro biological activities have been investigated and determined significant therapeutic potentials. Radical scavenging DPPH assay (79.4%), reducing power assay (62.68 ± 1.77%) and total antioxidant capacity (87.5 ± 4.8%) were evaluated to assess the antioxidative potential of Ag2ONPs. The disc diffusion method was adopted to evaluate the antibacterial and antifungal potentials of Ag2ONPs using different concentrations (125–1000 μg/mL). Moreover, the brine shrimp cytotoxicity assay was investigated and the LC50 value was calculated as 2.21 μg/mL. The biocompatibility assay using red blood cells (<200 μg/mL) confirmed the biosafe and biocompatible nature of Ag2ONPs. Alpha-amylase inhibition assay was performed and reported 66% inhibition. In conclusion, currently synthesized Ag2ONPs have exhibited strong biological potential and proved as an attractive eco-friendly candidate. In the future, this preliminary research work will be a helpful source and will open new avenues in diverse fields, including the pharmaceutical, biomedical and pharmacological sectors.